Research progress in catalytic oxidation of volatile organic compound acetone. Issue 4 (August 2021) - Mu, Xiaotian; Ding, Honglei; Pan, Weiguo; Zhou, Qi; Du, Wei; Qiu, Kaina; Ma, Junchi; Zhang, Kai
Abstract: Acetone, as a kind of typical volatile organic compounds (VOCs), is mainly discharged into the atmosphere through exhaust emissions, fuel combustion, pharmaceuticals, and printing, etc. It not only causes water pollution but also inhibits the people's central nervous system, posing a great threat to the ecological environment and human health. Due to its economy and compatibility, the catalytic oxidation method is considered to be one of the effective methods for removing acetone. The development of low-cost and high-efficiency catalysts can bring higher economic benefits. This review covers the research progress of acetone oxidation by noble metal and non-noble metal catalyst systems, and discusses the effects of metal composition, support, preparation method, and morphology on the catalyst activity. Comparison shows that both manganese-based and cobalt-based catalysts are the good substitutes for precious metal platinum-based and palladium-based catalysts, in which the concentration of oxygen vacancies, the number of active oxygen species, and the interaction between substrates are the key factors. In addition, the possible mechanism of catalytic oxidation of acetone is given, and the development of catalytic oxidation of acetone is prospected. Graphical Abstract: ga1 Highlights: Types of catalysts for acetone removal are summarized. Research development and mechanistic understanding of catalysts for acetone removal are overviewed. Mechanism of catalytic oxidation of acetone.